Serum keratin‐18 fragments as cell death biomarker in association with disease progression and prognosis in hepatitis B virus‐related cirrhosis. Issue 7 (3rd May 2019) - Cao, Zhujun; Chen, Liwen; Li, Jing; Liu, Yuhan; Bao, Rebecca; Liu, Kehui; Yan, Lei; Ding, Yezhou; Guo, Qing; Xiang, Xiaogang; Xie, Jingdong; Lin, Lanyi; et al.
Abstract: Extensive hepatocyte death leads to hepatic inflammation and contributes to systemic inflammation in decompensated cirrhosis. We aimed to investigate the prognostic value of serum cell death markers in patients with hepatitis B virus (HBV)‐related acute decompensation (AD) of cirrhosis with and without acute‐on‐chronic liver failure (ACLF). We studied two cohorts—cohort 1: 201 outpatients with stable chronic hepatitis B (49 cirrhosis); cohort 2: 232 inpatients with HBV‐related cirrhosis admitted for AD. Cell death was determined with serum keratin‐18 (K18) for total death and serum caspase‐cleaved‐K18 (cK18) for apoptosis. Survival analyses were performed using competing risk method. We found that serum K18 and cK18 were significantly ( P  < 0.001) higher in patients from cohort 2 than those from cohort 1. Among cohort 2, ACLF patients had significantly ( P  < 0.001) increased K18 and cK18 comparing to those without ACLF. Increased K18 and cK18 were mainly attributed to HBV flare and were associated with liver and coagulation failure. HBV‐AD patients without ACLF who admitted with upper tertile of K18 or cK18 were at higher risk of developing ACLF during follow‐up. Baseline serum K18 or cK18 was significantly associated with transplant‐free 90‐day survival independent of leucocytes, HBV DNA, bacterial infection, encephalopathy and severity scores. The combination of cell death biomarkers significantly improved the prognostic value of the currently established prognostic scores. The reduction of cell death level after standard treatment was associated with increased short‐term survival. In conclusion, measurements of serum K18 or cK18 in HBV decompensated cirrhosis are a promising tool for predicting ACLF and risk stratification of short‐term outcome.